Influence of Splitter Blades on the Flow Field of a Centrifugal Pump: Test-Analysis Comparison. (28th January 2007) - Kergourlay, G.; Younsi, M.; Bakir, F.; Rey, R.
Abstract : This work aims at studying the influence of adding splitter blades on the performance of a hydraulic centrifugal pump. The studied machine is an ENSIVAL-MORET MP 250.200.400 pump (diameter = 408 mm, 5 blades, specific speed = 32), whose impeller is designed with and without splitter blades. Velocity and pressure fields are computed using unsteady Reynolds-averaged Navier-Stokes (URANS) approach at different flow rates. The sliding mesh method is used to model the rotor zone motion in order to simulate the impeller-volute casing interaction. The flow morphology analysis shows that, when adding splitter blades to the impeller, the impeller periphery velocities and pressures become more homogeneous. An evaluation of the static pressure values all around the impeller is performed and their integration leads to the radial thrust. Global and local experimental validations are carried out at the rotating speed of 900 rpm, for both the original and the splitter blade impellers. The head is evaluated at various flow rates: 50%, 80%, 100%, and 120% of the flow rate at the best efficiency point (BEP). The pressure fluctuations are measured at four locations at the BEP using dynamic pressure sensors. The experimental results match the numerical predictions, so that the effect of adding splitter blades on the pump is acknowledged. Adding splitters has a positive effect on the pressure fluctuations which decrease at the canal duct.